Implementasi Kurikulum Merdeka pada Mata Pelajaran SKI di Madrasah Wilayah 3T Kabupaten Kepulauan Sangihe - Nurvina Darise, Gina; Mandiri, Elvira (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2025)
This study aims to examine the implementation of the Merdeka Curriculum in the teaching of Islamic Cultural History (SKI) at three madrasas located in Indonesia’s 3T regions (Outermost, Frontier, and Disadvantaged): MIN 2 Sangihe Islands, MTsN 1 Sangihe Islands, and MA Al-Aqsha Kendahe. The Sangihe Islands face unique geographical, socio-economic, and educational challenges that influence curriculum implementation. Employing a qualitative approach, data were collected through document analysis and in-depth interviews involving madrasa principals, curriculum vice principals, SKI teachers, and students. Findings indicate that implementation remains suboptimal due to several key challenges: (1) limited teacher capacity in developing teaching modules due to insufficient training; (2) lack of textbooks aligned with the new curriculum; (3) inadequate infrastructure, such as weak internet access and unstable electricity; and (4) a shortage of teachers, which hampers effective learning.The madrasas' stakeholders expect: (1) recruitment of more teachers through both civil servant (CPNS) and government contract (PPPK) schemes; (2) more comprehensive teacher training; (3) provision of appropriate textbooks; and (4) improvement of learning infrastructure.